Relationship between Work Environment and Patient Safety Culture - Akbar, Fuad Husain; Pasiga, Burhanuddin Daeng; Zain, Mazira Mohd; Arzahan, Intan Suraya Noor; Bahadin, Siti Azura; S, Senin M.; Jusoh, Juereanor Mat (CENTRAL ASIA AND THE CAUCASUS, 2022)
Background: The Agency of Health Care Research and Quality in assessing patient safety culture in hospitals have several aspects of dimensions that need to be considered, that is the expectations and actions of supervisors / managers in promoting patient safety, learning of continuous improvement, teamwork in units, open communication, feedback on errors, no-blame responses, adequate staffing, overall perception, hospital management support, inter-unit teamwork, patient submission and transfer and frequency of incident reportingMaterials and Methods: This study used a cross-sectional research design to obtain information about the relationship between the workplace environment and patient safety culture between resident physician and profession students. The sample (n = 105) consisted of 32 dental resident and 73 profession students. This questionnaire contained 34 questions that were distributed to subjects, data were collected and analyzed by SPSS software.Results: The work environment of dental hygienist has a close relationship with patient safety. Dental hygienist with 1-2 years of work experience, 2-8 years and more than 9 years have a significant relationship to patient safety culture. There was no statistically significant difference in the amount of work per week to the patient safety culture (P> 0.05).Conclusion: Among the work environment in the oral and dental hospital of Hasanuddin University, only 1 aspect had a significant effect on patient safety culture variables, that is work experience.